2006
DOI: 10.1108/00400910610710074
|View full text |Cite
|
Sign up to set email alerts
|

Just what are tomorrow's SME employees looking for?

Abstract: Purpose -The paper seeks to determine what tomorrow's employees (i.e. graduates) are seeking from SMEs in terms of organizational satisfaction and value characteristics. Design/methodology/approach -A survey of 55 university students who identified SMEs as their best opportunity for their career goals is shown. The survey utilized tested measures of organizational satisfaction and values. Findings -The paper finds that Generations X and Y are seeking equivalent values and satisfaction outcomes from SMEs. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
3
27
0
1
Order By: Relevance
“…In another study based in the United Kingdom, Broadbridge et al (2007) surveyed Gen Y students' expectations of retail employment and found that their major expectation was to enjoy their job, combined with concerns for fairness, tolerance and equity in the workplace. Szamosi (2006) found similar results when researching Gen Y students' expectations of employment with small and medium enterprises (SMEs), in that they wanted to work for Volume 15 2008 caring and sensitive SMEs that are environmentally concerned. These students also expected tangible and intangible rewards, empowerment, respect, workplace involvement, concern for employee welfare and supportive management.…”
Section: Generation Ysupporting
confidence: 71%
See 2 more Smart Citations
“…In another study based in the United Kingdom, Broadbridge et al (2007) surveyed Gen Y students' expectations of retail employment and found that their major expectation was to enjoy their job, combined with concerns for fairness, tolerance and equity in the workplace. Szamosi (2006) found similar results when researching Gen Y students' expectations of employment with small and medium enterprises (SMEs), in that they wanted to work for Volume 15 2008 caring and sensitive SMEs that are environmentally concerned. These students also expected tangible and intangible rewards, empowerment, respect, workplace involvement, concern for employee welfare and supportive management.…”
Section: Generation Ysupporting
confidence: 71%
“…In particular, how appealing is the typical hospitality job likely to be to the potential Gen Y candidate? Common themes uncovered in the academic research conducted thus far suggest Gen Y employees expect fairness, tolerance and equity Gursoy et al, 2008), involvement in the workplace (Gursoy et al, 2008;Szamosi, 2006), concern for employee welfare (Gursoy et al, 2008;Szamosi, 2006;Terjesen et al, 2007) and opportunities for training, development and work variety (Gursoy et al, 2008;Terjesen et al, 2007). The results of one of the few hospitality specific studies relating to Gen Y are not very encouraging: Barron et al (2007) found discrepancies between the work-related preferences and expectations of Gen Y hospitality students and the reality of work in the hospitality industry.…”
Section: Hospitality Employment and Generation Ymentioning
confidence: 93%
See 1 more Smart Citation
“…Within the OB literature, Organizational Satisfaction has been linked to Turnover Intention (Shore and Tetrick 1991;Kittiruengcharm 1997;Szamosi 2006). For example, Kittiruengcharm (1997) administered a survey to 408 public sector engineers in Thailand and found a significant negative correlation between Organizational Satisfaction and Turnover Intention.…”
Section: Replace Organizational Commitment With Organizational Satisfmentioning
confidence: 96%
“…In the exit interview, most employees disclose the reasons for leaving are due to meeting their demand of frequent changes (Shaw & Fairhurst, 2010) and looking for new excitement (Smola & Sutton, 2002). Menefee and Murphy (2004) found that the main reason for young employees having high level of intention to leave organizations are dissatisfaction with pay, dissatisfaction with management, inadequate opportunity for career-related skill development, dissatisfaction with benefits, uncomfortable work environment and conflicts with manager or co-workers (Szamosi, 2006).…”
Section: Intention To Leavementioning
confidence: 99%